Factors related to anxiety among resident doctors assigned to emergency room during the COVID-19 pandemic: a multivariate study at Sumatera Utara Affiliated Teaching Hospital - Elmeida Effendy; Ariwan Selian; Julius Martin Siagian (Medicinski glasnik, 2021)
Aim: To evaluate and assess knowledge and perception, as well as factors related to the occurrence of anxiety among frontliners, especially resident doctors working in emergency room (ER). Methods: This multivariate study was conducted with cross-sectional approach involving 80 eligible subjects (based on inclusion and exclusion criteria) that are consecutively assigned and assessed with GAD-7 questionnaire. The study was held in ER of Universitas Sumatera Utara affiliated teaching hospital from May to August 2020. Results: Our study found that variables such as nuptial status (p=0.032), seniority level (p=0.037), history of direct exposure to COVID-19 patients (p=0.001) and weekly work duration (p=0.002) were all statistically significant to correlate with the occurrence of anxiety among resident doctors assigned to work in ER. Conclusion: Acknowledgement of these factors might lead to proper and targeted support system strategies to address the anxiety issues among doctors, particularly those who work in ER during COVID-19 pandemic.
Keywords: anxiety; mental health; physicians